2008
DOI: 10.1002/psc.1047
|View full text |Cite
|
Sign up to set email alerts
|

Lipid interactions of acylated tryptophan‐methylated lactoferricin peptides by solid‐state NMR

Abstract: Lactoferricin (LfB) is a 25-residue innate immunity peptide released by pepsin from the N-terminal region of bovine lactoferrin. A smaller amidated peptide, LfB6 (RRWQWR-NH2) retains antimicrobial activity and is thought to constitute the "antimicrobial active-site" (Tomita, Acta Paediatr Jpn. 1994; 36: 585-91). Here we report on N-acylation of 1-Me-Trp5-LfB6, Cn-RRWQ[1-Me-W]R-NH2, where Cn is an acyl chain having n = 0, 2, 4, 6 or 12 carbons. Tryptophan 5 (Trp5) was methylated to enhance membrane binding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The CSAs of POPC (≈ 47 ppm ± 1 ppm) and POPE:POPG (3:1) (≈ 37 ppm ± 1 ppm) are furthermore unchanged in the presence of 1 mol % C6-LfB, indicating little observable perturbation of either the neutral or anionic lipid head groups. These findings support our previous results that acylated and Trp-methylated LfB peptides have little effect on the phosphate head groups of DMPC and DMPC:DMPG (3:1) bilayers even at 4 mol %[12]. Moreover, the MD simulations also show no change.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The CSAs of POPC (≈ 47 ppm ± 1 ppm) and POPE:POPG (3:1) (≈ 37 ppm ± 1 ppm) are furthermore unchanged in the presence of 1 mol % C6-LfB, indicating little observable perturbation of either the neutral or anionic lipid head groups. These findings support our previous results that acylated and Trp-methylated LfB peptides have little effect on the phosphate head groups of DMPC and DMPC:DMPG (3:1) bilayers even at 4 mol %[12]. Moreover, the MD simulations also show no change.…”
Section: Resultssupporting
confidence: 91%
“…The C6-LfB6 peptide was synthesized using solid-phase Fmoc methods on an Applied Biosystems (Foster City, CA) 433A peptide synthesizer using modified FastMoc® chemistry according to methods described in Greathouse et al [12] Peptide purity was assessed by reversed phase HPLC using a 4.6 × 50 mm Zorbax SB-C8 column packed with 3.5 μ l octylsilica (Agilent Technologies, Santa Clara CA), at 1 mL/min using a methanol/water gradient (including 0.1% TFA) from 10% to 60% over 8 min followed by a hold at 60% for 5 min. Chromatograms revealed a single major peak and mass spectrometry confirmed the correct mass (1084); therefore, the peptide was used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21A, Tables 3 and 5). Studies with a 1MeW-modified lactoferricin analog revealed enhanced membrane binding and showed 1MeW to be aligned at the membrane interface with an extent of motion similar to that of W [135]. Furthermore, the influence of dipole and quadrupole moments became apparent in intramolecular interactions between the -electrons of the indole ring of W with the positively charged guanidino moiety of R in RW-rich peptides, which were suggested to stabilize the structure of CAPs and enhance membrane binding [136,137].…”
Section: Role Of Sequence Composition Upon Bindingmentioning
confidence: 98%